The Influence of Marketing Mix on Purchasing Decisions Which Impact Consumer Loyalty in Online Pharmacies - Erna Susanti; Maura Linda Sitanggang; Nurita Andayani (SEAN Institute, 2024)
This research aims to analyze the influence of the marketing mix on purchasing decisions which have an impact on consumer loyalty in online pharmacies. This research uses a quantitative approach by collecting data through questionnaires distributed to 100 respondents who are online pharmacy users in the DKI Jakarta area. Data analysis is carried out in order to process data more thoroughly and accurately so as to obtain the expected results. The model used in this research is the causality model and to test the hypothesis proposed in this research the analysis technique used is SEM (Stuctural Equation Modelling). The research results show 1) The influence of online pharmacy marketing mix on purchasing decisions: Product variables have no influence on purchasing decisions; Price variables have an influence on purchasing decisions; Distribution variables have an influence on purchasing decisions; Promotional variables that influence purchasing decisions. 2) The influence of online pharmacy marketing mix on consumer loyalty: Product variables have an influence on consumer loyalty; Product variables have an influence on consumer loyalty; Distribution variables have no influence on consumer loyalty; Promotion variables have no influence on consumer loyalty. 3) The influence of the impact of purchasing decisions on consumer loyalty, meaning that if there is an increase in purchasing decisions, it will increase consumer loyalty